1998
DOI: 10.4269/ajtmh.1998.58.75
|View full text |Cite
|
Sign up to set email alerts
|

Testing for anti-circumsporozoite and anti-blood-stage antibodies for epidemiologic assessment of Plasmodium falciparum infection in travelers.

Abstract: Abstract. The purpose of this investigation was to assess the role of serology for establishing incidences of Plasmodium falciparum malaria and of exposure to P. falciparum in epidemiologic studies of travelers using chemoprophylaxis. The design was a prospective cohort study involving 548 short-term Dutch travelers to areas endemic for P. falciparum malaria. Sera were collected before departure and, together with the medical history, 2-6 weeks after return. All sera were tested for anti-circumsporozoite (CS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…Among them, only 2% had experienced a clinical malaria attack [22]. Others have reported that travellers from malaria-free countries can develop antibody response against pre-erythrocytic [20,21] and blood stages [32] P. falciparum antigens without progressing to a symptomatic illness. Thus, the characterization of erythrocytic stage antigens specifically detected by healthy adults shortly exposed to malaria and under chemoprophylaxis could be informative to estimate individual exposure to malaria transmission, and to clarify the mechanisms involved in the development of immune responses after malaria infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, only 2% had experienced a clinical malaria attack [22]. Others have reported that travellers from malaria-free countries can develop antibody response against pre-erythrocytic [20,21] and blood stages [32] P. falciparum antigens without progressing to a symptomatic illness. Thus, the characterization of erythrocytic stage antigens specifically detected by healthy adults shortly exposed to malaria and under chemoprophylaxis could be informative to estimate individual exposure to malaria transmission, and to clarify the mechanisms involved in the development of immune responses after malaria infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several blood stage antigens have been characterized, and some of them are candidates for vaccine trials (for review [18,19]). Although some studies have assessed the antibody response to pre-erythrocytic antigens in travellers [20-22], seldom data are available concerning the antibody response against blood stage antigens from non-immune healthy adults briefly exposed to malaria transmission, such as travellers or individuals living in area where malaria is under elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Compliance regarding protection against mosquito bites was recorded as self-reported use and defined as having applied two or more of the four measures mentioned in the leaflet. (Cobelens et al 1997). Travel destinations were grouped into 5 regions that corresponded to the classification used by the World Health Organization (1991).…”
Section: Definitionsmentioning
confidence: 99%
“…These methods have included malaria antigen detection using tagged monoclonal antibodies, fluorescence microscopy, flow cytometry, automated analysis of blood cells, quantitative buffy coat inspection, acridine orange staining, serology-antibody detection, molecular amplification methods, and laser desorption mass spectrometry (1,17,21,24,31,40,62,68,82,95). Remote microscopic diagnosis via telemedicine has also been evaluated, but imaging quality and infrastructure requirements pose challenges (67).…”
Section: Alternative Malaria Diagnosismentioning
confidence: 99%